AB0768 Levamisole/cocaine-related vasculopathy: Autoantibody specificities in 4 patients. (23rd January 2014) - Walsh, N.M.; Green, P.J.; Burlingame, R.W.; Hanly, J.G.
Abstract : Background: The spectrum of autoantibody-associated vasculitis includes a newly recognized syndrome induced by levamisole-adulterated cocaine (L/CS). Emerging data has incriminated levamisole as the culprit. The syndrome is characterized clinically by purpuric skin changes, arthralgia or arthritis and systemic symptoms in a cocaine-user, combined with the presence of autoantibodies and occasionally neutropenia. The spectrum of autoantibodies in this setting has been variable. Of interest, antibodies to human neutrophil elastase (HNE), an uncommon subset of anti-neutrophil cytoplasmic antibodies (ANCA), have been linked with cocaine-related inflammatory conditions and because there can be concomitant low reactivity with the common ANCA specificities (proteinase 3 [PR3] and myeloperoxidase [MPO]) confusing results can be generated in clinical laboratory assays. Objectives: We aimed to examine the autoantibody specificities, particularly for anti-nuclear antibodies (ANAs) and ANCAs, in 4 patients with the L/CS to determine (i) if a consistent profile can be identified, (ii) to compare results for ANCA obtained in a clinical laboratory and in a research immunology laboratory and (iii) to establish whether the presence of the antibodies corresponds with concurrent cocaine use and/or active disease. Methods: In the clinical laboratory ANA (dsDNA, Chromatin, Riposomal P, Ro, La, Centromere, Sm, Sm/RNP, Scl-70, and Jo-1) and ANCA (PR3 and MPO) were evaluated by multiplex flow immunoassay (Bio Plex 2200). In the research immunology laboratory a broad panel of ANCA target antigens (azurocidin, BPI, catalase K, cathepsin G, defensins, elastase, lactoferrin, lysozyme, MPO and PR3) was evaluated by ELISA. Results: Nineteen serum samples from 4 female users of crack cocaine with the L/CS were examined. Urine toxicology for levamisole was positive in each case. The mean age was 41 years (range: 32-49). All 4 patients had purpuric skin changes of varying severity, arthralgia or arthritis, malaise and positive autoimmune serology. Two had a remitting and relapsing course and the mean follow-up period was 8 months (range 0-12). Serological tests in the clinical laboratory indicated that all 4 patients were ANA+ with specificity for chromatin in 4 and Ro in 1. In the same laboratory, evaluation of sequential samples for ANCA showed inconsistent dual positivity for MPO and PR3 in 3 cases. Determination of ANCA target antigen specificities in the research immunology laboratory revealed borderline dual positivity for PR3 and MPO in 2 patients. Anti-HNE antibodies were found in 3 cases and anti-lactoferrin in 4. A temporal association between the presence of any of the antibodies and use of cocaine or active disease was not demonstrated. Conclusions: Data from this small but well characterized population suggests that, in an appropriate clinical setting, a positive ANA with specificity for chromatin and a positive ANCA with specificity for HNE and/or lactoferrin support a diagnosis of the L/CS. Despite their potential diagnostic utility these serological tests are not reliable biomarkers of concurrent cocaine use or active disease. Disclosure of Interest: None Declared